SANTRI'S PERCEPTION TOWARDS KITAB KUNING LEARNING METHODS AT AS'ADIYAH SENGKANG ISLAMIC BOARDING SCHOOL - Muslihin Sultan; A. Fajar Awaluddin; Muh. Subair (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
Research on the method of kitab kuning learning has been widely carried out by many scholars, yet there is still a lack of research examining how to read the kitab kuning with the mumtaz method quickly. To complement the existing research, this study investigates the perception of As'adiyah Sengkang Islamic boarding school students towards Mumtaz learning methods. Using a perception case study research design, the study reported three things. First, Mumtaz's learning included ten chapters of material that began with recognizing word and keyword identity, vocabulary, verb change and ended with a change in the final line of words in the form of kitab kuning reading practices. Second, the application of the Mumtaz method consists of four stages, and third, the perception of students towards the Mumtaz learning method is positive and negative. Positive perception occurs because Mumtaz's material is easy to understand, and the learning method is quite fun because it always uses rhythmic songs. On the other hand, negative perceptions occur not because of the material problems and learning methods but because of a short duration of time and not directly applied to the kitab kuning, but partial book-based examples. This research implies that this learning method is worth applying and disseminating in various Islamic universities in Indonesia.